Evaluation of whole cell antigen and outer memberane protein based latex agglutination test for serodiagnosis of canine leptospirosis - Sariprabha P (Department of Veterinary Microbiology,College of Veterinary and Animal Sciences, 2010)
A study was undertaken to evaluate the efficacy of whole cell antigen and OMP based Latex Agglutination Test (LAT) for the serodiagnosis of canine leptospirosis. Serum samples were collected from University Veterinary Hospitals of Mannuthy and Kokkali. These samples were subjected to serologic testing by Microscopic Agglutination Test (MAT) and LAT and the results were compared.